Development of a linear programming module based on the dick and carey program to improve problem solving skills of students at the faculty of teacher training and education Batanghari university Jambi - Zulyadaini, Zulyadaini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the learning process, lecturers provide materials in teaching mode, and students only listen to lectures and concentrate on lectures. The lecture model is still used because students always have difficulties in understanding the material when given assignments or modules. This study aims to develop a linear program module/teaching material that meets the needs of the students of teacher training and education faculty, used the research and development (R&D) method with the Dick and Carey model. The subjects were the students of teacher training and education faculty in the 4th semester of the 2019/2020 academic year, totaling 10 students from Batanghari University, Jambi. The results showed that based on the experts' validation of the module was its effectiveness in increasing students' understanding or how it compared to the previous module. The feasibility percentage of design validation; 93.3%, media validation; 91.3%, and material validation; 93.7%; followed by the one-to-one test with percentage of 93.7%, the group test; 93.5%, and the field test; 87%. In conclusion, the development of linear programming module is feasible and can be used for students of teacher training and education faculty. The implication of this research is that it can be used as a description of the creation of a module using the research and development (R&D) method with the Dick and Carey model.